Detection of Aeromonas hydrophila using fiber optic microchannel sensor - Gauri, Samla; Zainal Abidin, Zurina; Kamuri, Mohd Firdaus; Mahdi, Mohd Adzir; Md Yunus, Nurul Amziah (Hindawi Publishing Corporation, 2017)
This research focuses on the detection of Aeromonas hydrophila using fiber optic microchannel biosensor. Microchannel was fabricated by photolithography method. The fiber optic was chosen as signal transmitting medium and light absorption characteristic of different microorganisms was investigated for possible detection. Experimental results showed that Aeromonas hydrophila can be detected at the region of UV-Vis spectra between 352 nm and 354 nm which was comparable to measurement provided by UV spectrophotometer and also theoretical calculation by Beer-Lambert Absorption Law. The entire detection can be done in less than 10 minutes using a total volume of 3 μL only. This result promises good potential of this fiber optic microchannel sensor as a reliable, portable, and disposable sensor.